Evaluating variability in rhythmic gymnastics: Analysis of split leap using the gold standard motion analysis system - Coppola, S.; Costa, C.; Albano, D.; Vastola, R. (Journal of Human Sport & Exercise, 2025)
Recent research suggests that variability enhances motor control, learning, and adaptation by improving the system's response to environmental demands. It also develops the cognitive and executive functions of athletes. The purpose of the study is to evaluate the variability of the split leap in rhythmic gymnastics, performed with and without ribbon handling, analysing in which of the two techniques there is greater variability. The sample consists of six competitive gymnasts with an average age of 15.1 years (±0.94). The acquisitions were carried out with the BTS Bioengineering integrated multifactorial optoelectronic system, using fifteen passive markers, six BTS Smart-DX cameras, two cameras for video support and seven BTS-6000 force platforms. The results show that the coefficient of variation (CV%) in trials performed with ribbon is higher than those without the apparatus. Cohen's Effect Size revealed a small effect size between trials with ribbon and those without. Despite being minimal, this difference emphasizes the presence of variability in jumps executed with ribbon in comparison to free body trials. In conclusion, this study explored both intrinsic (CV%) and extrinsic (task complexity, technical experience) factors of jump performance, highlighting the utility of gold standard motion analysis systems for researching executive variability in rhythmic gymnastics jumps.